Highly frequent promoter methylation and PIK3CA amplification in non-small cell lung cancer (NSCLC) - Shi Bingyin (BMC Cancer, 2011)
Abstract Background Lung cancer is the leading cause of cancer-related death worldwide. Genetic and epigenetic alterations have been identified frequently in lung cancer, such as promoter methylation, gene mutations and genomic amplification. However, the interaction between genetic and epigenetic events and their significance in lung tumorigenesis remains poorly understood. Methods We determined the promoter methylation of 6 genes and PIK3CA amplification using quantitative methylation-specific PCR (Q-MSP) and real-time quantitative PCR, respectively, and explore the association of promoter methylation with PIK3CA amplification in a large cohort of clinically well-characterized non-small cell lung cancer (NSCLC). Results Highly frequent promoter methylation was observed in NSCLC. With 100% diagnostic specificity, excellent sensitivity, ranging from 45.8 to 84.1%, was found for each of the 6 genes. The promoter methylation was associated with histologic type. Methylation of CALCA, CDH1, DAPK1, and EVX2 was more common in squamous cell carcinomas (SCC) compared to adenocarcinomas (ADC). Conversely, there was a trend toward a higher frequency of RASSF1A methylation in ADC than SCC. In addition, PIK3CA amplification was frequently found in NSCLC, and was associated with certain clinicopathologic features, such as smoking history, histologic type and pleural indentation. Importantly, aberrant promoter methylation of certain genes was significantly associated with PIK3CA amplification. Conclusions Our data showed highly frequent promoter methylation and PIK3CA amplification in Chinese NSCLC population, and first demonstrated the associations of gene methylation with PIK3CA amplification, suggesting that these epigenetic events may be a consequence of overactivation of PI3K/Akt pathway.